2011
DOI: 10.1007/s11764-011-0199-1
|View full text |Cite
|
Sign up to set email alerts
|

How confident are young adult cancer survivors in managing their survivorship care? A report from the LIVESTRONG™ Survivorship Center of Excellence Network

Abstract: Introduction This study examined the association between sociodemographic, cancer treatment, and care delivery factors on young adult cancer survivors’ confidence in managing their survivorship care. Methods Survivors aged 18-39 years (n=376) recruited from the LIVESTRONG™ Survivorship Center of Excellence Network sites completed a survey assessing self-reported receipt of survivorship care planning, expectations of their providers, and confidence in managing their survivorship care. Multivariate logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…Another study has shown that treatment summaries are associated with more accurate survivor knowledge about breast and colorectal cancer diagnoses and the treatment they received [24]. Our results agree with other findings [25] that SCPs are associated with feelings of self-efficacy. We were unable to demonstrate compelling evidence of a mediating effect of self-efficacy on outcomes, however.…”
Section: Discussionsupporting
confidence: 91%
“…Another study has shown that treatment summaries are associated with more accurate survivor knowledge about breast and colorectal cancer diagnoses and the treatment they received [24]. Our results agree with other findings [25] that SCPs are associated with feelings of self-efficacy. We were unable to demonstrate compelling evidence of a mediating effect of self-efficacy on outcomes, however.…”
Section: Discussionsupporting
confidence: 91%
“…Each of the studies is summarized in Table 4. 30, 5064 Three of these were randomized controlled trials (RCT) and 11 were observational studies, including eight survivor surveys 54, 58, 61, 62, 6568, 69 and two interview studies of survivors 30, 63, 63 and oncology providers. 63 Two observational studies analyzed administrative data.…”
Section: Resultsmentioning
confidence: 99%
“…58, 70, 60 Five observational studies included a comparison group that either reflected survivor outcomes prior to an SCP intervention 60, 61 or a concurrent group of survivors that did not receive an SCP. 54, 59, 71 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Good care coordination between the multiple providers involved in a survivor's care will be paramount to appropriately addressing the concerns. 27,[32][33][34] Ongoing developments in electronic health information exchange (that is, electronic and personal health records) might help facilitate this kind of multidisciplinary care, and research suggests that cancer survivors believe that electronic health information exchange will help improve coordination in cancer care. 35 Developing a multidisciplinary approach that addresses the complex nature of posttreatment survivorship is not an easy task.…”
Section: Ruth Rechis Sarah R Arvey and Ellen Burke Beckjordmentioning
confidence: 99%